Effects of in vivo hyperthermia on natural killer cell activity, in vitro proliferative responses and blood mononuclear cell subpopulations. - Kappel, M (1991)
This work was designed to test the hypothesis that elevations in body temperature of humans induce immunostimulation. Eight healthy volunteers were immersed in a water bath (water temperature 39.5 degrees C) for 2 h, during which their rectal temperature rose to 39.5 degrees C. On a later day they served as their own controls, being immersed into thermoneutral water (34.5 degrees C) for 2 h. Blood samples were collected before immersion, at body temperatures of 38 degree C, 39 degree C and 39.5 degree C, and 2 h after water immersion. The interleukin-2 (IL-2) enhanced natural killer (NK) cell activity (lysis per fixed number of mononuclear cells), as well as the proportion and total number of NK cells (CD16+ cells), increased significantly during hyperthermia compared with control values. The lymphocyte proliferative responses did not differ significantly between hyperthermia and thermoneutral conditions. The proportion of pan-T (CD3+) cells was maximally depressed 2 h after water immersion. The decreased proportion of CD3+ cells was mainly due to a decreased percentage of CD4+ cells (not significant). The proportion of B cells (CD19+ cells) did not fluctuate significantly, while a marked and significant increase in monocyte proportion (CD14+ cells) was found 2 h after hyperthermia. Two hours after hot water immersion the lymphocyte concentration declined while the neutrophil and monocyte concentrations were augmented. Induced hyperthermia causes significantly increased serum cortisol, plasma norepinephrine and plasma epinephrine concentrations compared to controls. It is possible that the altered immune functions induced by elevated body temperature can be ascribed to altered composition and function of blood mononuclear cells induced by elevated levels of stress hormones.